The contribution of the unfolded protein response (UPR) to chronic kidney disease development in a mouse model - Mohammed-Ali, Zahraa (My University, 2017)
Presently, there is a significant need to develop therapeutics to combat chronic kidney disease (CKD) due to the rise in its prevalence along with the burden of disease it conveys to the patients that suffer from CKD. Further, it’s association with comorbities including hypertension and cardiovascular disease contribute to CKD’s adverse effects on human health. Experimental and clinical evidence points to a role for endoplasmic reticulum (ER) stress in pathogenesis of CKD, however, the mechanism by which ER stress components ameliorate CKD in animal studies have not been fully elucidated. The research presented in this thesis has explored the impact of modulating the ER stress responses on CKD development. A central focus in this thesis involved investigating the pathways regulated during ER stress inhibition and the identification of therapeutic targets that could be used to treat CKD. Firstly, a model of CKD in the C57BL/6 mouse was established (Chapter 2). This model involved a uninephrectomy combined with Angiotensin (Ang) II and deoxycorticosterone acetate (DOCA) infusion and high salt diet. This model overcame the resistance of C57BL/6 mice against CKD development and allowed the use of genetic knockout mice that are commonly available on the C57BL/6 background. Moreover, the Ang II/DOCA salt model exhibited key features of human CKD within 21 days including proteinuria, glomerulosclerosis, renal interstitial fibrosis, inflammation and apoptosis. A time point analysis of the Ang II/DOCA salt model showed that ER stress was upregulated in the kidneys within 7 days along with the occurrence of proteinuria, fibrosis and inflammation (Chapter 3). Treatment with 4-phenyl butyric acid (4-PBA), a small molecular weight chaperone, used to alleviate ER stress, resulted in attenuated hypertension, proteinuria, glomerulosclerosis, fibrosis and inflammation. Further investigation showed that 4-PBA halted CKD progression through its effect on 1) the glomeruli, where 4-PBA treated mice had lower glomerulosclerosis and 2) the tubules, where 4-PBA resulted in an increased level of cubilin available on the membranes for the reabsorption of hyperfiltered albumin in CKD (Chapter 3). When the Ang II/DOCA salt model was applied to mice deficient in CHOP, a pro-apoptotic gene upregulated by ER stress, glomerulosclerosis, proteinuria, fibrosis and inflammation were significantly reduced compared to wildtype (WT) mice. CHOP deficient mice were shown to have higher levels of nephrin, an important component of the renal filtration barrier and thus greater glomerular structure integrity than WT mice and improved CKD. Chapter 4 of this thesis describes the effects of heterozygosity in GRP78, the key regulator of the unfolded protein response (UPR) on Ang II/DOCA salt-induced CKD. GRP78+/- mice showed lower proteinuria, fibrosis and macrophage infiltration than WT mice. Collectively, the data discussed in this thesis presents potential therapeutic targets within the UPR and demonstrates pharmacological ER stress inhibition as a strategy to ameliorate CKD.